Bellman-ford and greedy algorithms to optimize the shortest route of PT. TIKI Jalur Nugraha Ekakurir (JNE) - Putri Harahap, Riska Evita; Husein, Ismail (Universitas Islam Negeri Raden Intan Lampung, 2024)
The purpose of this research is to find a comparison of Bellman-Ford and Greedy algorithms to optimize the shortest route of PT Tiki Jalur Nugraha Ekakurir (JNE). Bellman-Ford and Greedy algorithms are two algorithms that are often used in finding the shortest distance or optimal solution on a weighted graph. This research will be carried out at the JNE Medan Representative Office located on Jl. SM Raja Km 10.5 Amplas Trade Center Complex Blok F-10, while the type of research that will be used in this paper is applied research. The results of the study indicated the selection of the Bellman-Ford method because the Bellman-Ford method provides a more optimal route in terms of distance. Where the total initial distance used by PT Tiki Jalur Nugraha Ekakurir (JNE) is 20.5 km through routes including A→C → D → E → G→ H → J→ K→ L → N → O → P → R. While the total distance from the results of the new route sequence using the Bellman-Ford algorithm is 17.3 km by going through routes including A→B→D→E→F→H→I→K→L→M→O→Q→R And the total distance of the new sequence results using the Greedy algorithm is 17.5 km by going through routes A→B → D → E → F→ H → J→ K→ L → N → O → Q → R. This shows an efficiency of 15% in comparing existing routes with routes resulting from data analysis using Bellman-Ford.